1983
DOI: 10.1113/jphysiol.1983.sp014634
|View full text |Cite
|
Sign up to set email alerts
|

A role for an indoleamine other than 5‐hydroxytryptamine in the hypothalamic thermoregulatory pathways of the rat

Abstract: 1. Intrahypothalamic injection of either 5‐hydroxytryptamine (5‐HT) (20 μg) or tryptamine (1 μg) caused hypothermia and hyperthermia respectively in lightly restrained rats maintained at an ambient temperature of 20 ± 1 °C. 2. Both the 5‐HT‐ and the tryptamine‐sensitive sites were located within the same region of the preoptic area. 3. When rats were tested at different ambient temperatures (4, 20 and 29 °C), intrahypothalamic injection of 5‐HT caused a marked fall in core temperature (‐1·3 °C) in rats maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…These nuclei send serotonergic nerve fibers to many other brain areas, such as the olfactory bulb, hypothalamus, thalamus, hippocampus, amygdala, and cerebral cortex [ 45 ]. Since the 1960s, several studies have attempted to clarify the role of serotonin signaling in the POAH for body temperature with contradictory results i.e., [ 44 , 47 ]. In 2004, Ishiwata et al concluded that POAH may not be the main location for thermoregulatory signaling of serotonin, as external infusion of serotonin in the POAH did not affect body temperature, nor did heat exposure change the serotonin release in this brain area in their experiment [ 48 ].…”
Section: Behavioral State Neurotransmittersmentioning
confidence: 99%
“…These nuclei send serotonergic nerve fibers to many other brain areas, such as the olfactory bulb, hypothalamus, thalamus, hippocampus, amygdala, and cerebral cortex [ 45 ]. Since the 1960s, several studies have attempted to clarify the role of serotonin signaling in the POAH for body temperature with contradictory results i.e., [ 44 , 47 ]. In 2004, Ishiwata et al concluded that POAH may not be the main location for thermoregulatory signaling of serotonin, as external infusion of serotonin in the POAH did not affect body temperature, nor did heat exposure change the serotonin release in this brain area in their experiment [ 48 ].…”
Section: Behavioral State Neurotransmittersmentioning
confidence: 99%
“…However, there is contradiction that the same Tb change is not obtained in spite of having medicated PO/AH with the same 5-HT agents (Clark and Lipton, 1986). For example, although Feldberg and Myers (1963) reported Tb increase after 5-HT microinjection into the PO/AH, Cox et al (1983) reported Tb decrease after the same procedure. Thus, the exact role of 5-HT in the PO/AH in thermoregulation is not established yet due to conflicting results probably related to experimental techniques or conditions such as the use of anesthesia.…”
Section: Discussionmentioning
confidence: 87%
“…For example, Cox et al (1983) reported Tb decrease after 5-HT microinjection into the PO/AH. Clark and Lipton (1986) reviewed different results of Tb response after microinjection of 5-HT into the PO/AH and concluded that the role of 5-HT in the PO/AH in thermoregulation is obscure.…”
Section: Introductionmentioning
confidence: 95%
“…Blockade of 5-HT synthesis resulted in the inability to regulate CBT in rats [34]. Additionally, intrahypothalamic injection of 5-HT caused a marked decreased in CBT in rats [35]. However, another study found no direct correlation between changes in CBT and subsequent changes in 5-HT or levels of its metabolite, 5-HIAA, in the hypothalamus [36].…”
Section: Discussionmentioning
confidence: 99%